(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
One of the most prominent and striking feature of today’s globalised world is theexponential growth of FDI in both developed and developing countries. In thelast two decades the pace of FDI flows are rising faster than almost all other indicators of economic activity worldwide. Developingcountries, in particular, considered FDI as the safest type of external finance as it not only supplement domestic savings, foreign reserves but promotes growth even more through spillovers of technology, skills, increased innovative capacity, anddomestic competition. Now a days, FDI has become an instrument of internationaleconomic integration.